Exploration of extracellular vesicles from Ascaris suum provides evidence of parasite–host cross talk. Issue 1 (14th February 2019) - Hansen, Eline P.; Fromm, Bastian; Andersen, Sidsel D.; Marcilla, Antonio; Andersen, Kasper L.; Borup, Anne; Williams, Andrew R.; Jex, Aaron R.; Gasser, Robin B.; Young, Neil D.; Hall, Ross S.; Stensballe, Allan; et al.
ABSTRACT: The prevalent porcine helminth, Ascaris suum, compromises pig health and reduces farm productivity worldwide. The closely related human parasite, A. lumbricoides, infects more than 800 million people representing a disease burden of 1.31 million disability‐adjusted life years. The infections are often chronic in nature, and the parasites have a profound ability to modulate their hosts' immune responses. This study provides the first in‐depth characterisation of extracellular vesicles (EVs) from different developmental stages and body parts of A. suum and proposes the role of these vesicles in the host–parasite interplay. The release of EVs from the third‐ (L3) and fourth‐stage (L4) larvae and adults was demonstrated by transmission electron microscopy (TEM), and sequencing of EV‐derived RNA identified a number of microRNAs (miRNAs) and transcripts of potential host immune targets, such as IL‐13, IL‐25 and IL‐33, were identified. Furthermore, proteomics of EVs identified several proteins with immunomodulatory properties and other proteins previously shown to be associated with parasite EVs. Taken together, these results suggest that A. suum EVs and their cargo may play a role in host–parasite interactions. This knowledge may pave the way to novel strategies for helminth infection control and knowledge of their immune modulatory potential.